The effect of collagen hydrogel on 3D culture of ovarian follicles. (11th November 2016) - Joo, Sunyoung; Oh, Seh-Hoon; Sittadjody, Sivanandane; Opara, Emmanual C; Jackson, John D; Lee, Sang Jin; Yoo, James J; Atala, Anthony
Abstract: The in vivo function and phenotype of ovarian follicle cells are determined by many factors. When these cells are removed from the in vivo microenvironment and grown in a 2D in vitro environment, the function of the follicular cells is difficult to preserve. A collagen hydrogel was used to examine the hormone and oocyte maturation of ovary follicles in a 3D culture system. Ovarian follicles from rats were isolated and cultured in various concentration of type I collagen hydrogels ranging from 1% to 7% (weight/volume). Differences in cell survival, follicle growth and development, sex hormone production, and oocyte maturation were seen with the modifications in the collagen hydrogel density and elasticity. The results show the significance of the collagen hydrogel properties on phenotype and function maintenance of the ovarian follicles in a 3D culture system.